Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00125-008-1060-6
|View full text |Cite
|
Sign up to set email alerts
|

The HMG-CoA reductase inhibitor rosuvastatin and the angiotensin receptor antagonist candesartan attenuate atherosclerosis in an apolipoprotein E-deficient mouse model of diabetes via effects on advanced glycation, oxidative stress and inflammation

Abstract: Aims/hypothesis We evaluated the anti-atherosclerotic effect of the 3-hydroxy-3-methylglutaryl CoA reductase inhibitor, rosuvastatin, and the angiotensin II receptor blocker (ARB), candesartan, alone and in combination, in the streptozotocin-induced diabetic apolipoprotein Edeficient (Apoe −/− ) mouse. Methods Control and streptozotocin-induced diabetic Apoe −/− mice received rosuvastatin (5 mg kg −1 day −1 ), candesartan (2.5 mg kg −1 day −1 ), dual therapy or no treatment for 20 weeks. Aortic plaque depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 52 publications
0
39
1
1
Order By: Relevance
“…Certain antihypertensive and lipid-lowering drugs may affect AGEs metabolism. 19,20 However, (multivariate) linear regression analysis of SAF does not suggest such an effect in our cohort. Stratification of the results of the Cox regression analyses by the use of these drugs would have been interesting.…”
Section: Skin Autofluorescence In Peripheral Artery Diseasecontrasting
confidence: 66%
“…Certain antihypertensive and lipid-lowering drugs may affect AGEs metabolism. 19,20 However, (multivariate) linear regression analysis of SAF does not suggest such an effect in our cohort. Stratification of the results of the Cox regression analyses by the use of these drugs would have been interesting.…”
Section: Skin Autofluorescence In Peripheral Artery Diseasecontrasting
confidence: 66%
“…Yoshida et al [26] suggested that telmisartan, an angiotensin II type I receptor blocker, acts as an anti-inflammatory agent against AGE by suppressing RAGE expression via pepoxisome proliferator-activated receptor-gamma activation. Statins and the angiotensin II type I receptor blocker were reported to attenuate atherosclerosis via their effects on advanced glycation, oxidative stress, and inflammation in an animal model [27]. Acute modulation by these cardiovascular agents in patients with acute stroke has not been clarified.…”
Section: Discussionmentioning
confidence: 98%
“…Mice successfully induced with EAM (n030) were divided into three groups: non-treated EAM group (group N, n010); low-dose rosuvastatin group (1 mg/kg/day, group L, n010), and high-dose rosuvastatin group (10 mg/kg/day, group H, n010). The rosuvastatin dosages were determined from reports of previous work [9,10]. Rosuvastatin therapy started at the same time of immunization.…”
Section: Model Of Eam and Medicationmentioning
confidence: 99%